2019
DOI: 10.1002/etc.4537
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Impact of Manufacturing Processes on the Ecotoxicity of Carbon Nanofibers: A Multi–Aquatic Species Comparison

Abstract: Manufactured nanomaterial production is outpacing the ability to investigate environmental hazard using current regulatory paradigms, causing a backlog of materials requiring testing. To ameliorate this issue, regulatory bodies have proposed integrating safety into the production of novel nanomaterials, allowing for hazards to be identified early in development rather than aftermarket release. In addition, there is a growing interest in short‐term ecotoxicity testing to rapidly identify environmental hazards. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 33 publications
(39 reference statements)
0
13
0
Order By: Relevance
“…Other critical issues that were identified by some of the authors are: (i) graphene material hetero-aggregation with algae and precipitation out of the water column (Marković et al, 2020); (ii) shading effects of the test dispersions on growth and/or nutrient depletion due to adsorption to graphene materials (Malina et al, 2019); and (iii) interferences with fluorescent readouts at high test material concentrations (Barrick et al, 2019;Malina et al, 2019;Marković et al, 2020). These three points are discussed herein.…”
Section: Freshwater Alga and Cyanobacteria Growth Inhibitionmentioning
confidence: 97%
See 2 more Smart Citations
“…Other critical issues that were identified by some of the authors are: (i) graphene material hetero-aggregation with algae and precipitation out of the water column (Marković et al, 2020); (ii) shading effects of the test dispersions on growth and/or nutrient depletion due to adsorption to graphene materials (Malina et al, 2019); and (iii) interferences with fluorescent readouts at high test material concentrations (Barrick et al, 2019;Malina et al, 2019;Marković et al, 2020). These three points are discussed herein.…”
Section: Freshwater Alga and Cyanobacteria Growth Inhibitionmentioning
confidence: 97%
“…32 and 84 mg/L, for -COOH and -NH 2 functionalised G, respectively) (Zhang et al, 2018). The graphene nanofiber tested (GANF®) and nanofibers produced through superheating (GANFg) and a scaled up production process of GANF® (GATam) had EC 50 72h values of 3.09, 8.48, and 2.12 mg/ L, respectively (Barrick et al, 2019). This influence of production process on effects was also evidenced in the case of different production methods used for GO with EC 50 values of 0.5, 14 and 10 mg/L according to the distinct production methods used (Hoffman, Hummers, and Tour, respectively) (Malina et al, 2019).…”
Section: Freshwater Alga and Cyanobacteria Growth Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it was reported that NPs can enter the environment during their manufacturing, utilization, and disposal [ 16 ]. A large and growing body of literature has investigated the aquatic toxicity of carbon nanotubes [ 17 , 18 ], carbon nanofibers [ 19 ], silicon NPs [ 20 ], and metal-based NPs [ 21 , 22 ] in different model organisms. However, it is still difficult to understand the mechanisms of toxicity and behavior of different types of nanomaterials in aquatic systems.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that with an increasing annual production of CNFs, the risks of their harmful influence to the environment and human health is rising. Many research works have been devoted to studying of environmental toxicity of different nanomaterials including CNF [ [8] , [9] , [10] , [11] , [12] ]. However, the toxic properties of CNF are still not fully understood.…”
Section: Introductionmentioning
confidence: 99%